The law regulating beneficiary funds in South Africa : a critical analysis - Mangammbi, Mafanywa Jeffrey (My University, 2013)
This mini-dissertation evaluates the laws regulating beneficiary funds in South Africa. A beneficiary fund is a fund established for the purposes of accepting lump sum death benefits awarded in terms of Section37C of the Pension Funds Act (the Act) to a beneficiary (dependant or nominee) on the death of a member, which are not paid directly to that beneficiary or to a trust nominated by the member, or to the member’s estate or to the guardian’s fund. This replaces the previous payments to trusts and a fund can now only pay to a trust if the trust was nominated by the member, a major dependant or nominee; a person recognised in law or appointed by a court as the person responsible for managing the affairs or meeting the daily care needs of a minor or incapacitated major dependant or nominee. Any association of persons or business carried on under a fund or arrangement established with the object of receiving, administering, investing and paying benefits, referred to in section 37C on behalf of beneficiaries, payable on the death of more than one member of one or more pension funds is a beneficiary fund and must be registered by the Financial Services Board and approved. Beneficiary funds were introduced as a result of the amendments to the Pension Funds Act into the Financial Services Laws General Amendment Act, 22 of 2008. The beneficiary funds were introduced with stronger regulatory framework. They have sufficient governance, reporting requirements and conduct annual audits.
Thesis (LLM. (Labour Law)) -- University of Limpopo, 2013
Keywords: Pension funds; Social security; Pensions -- Law and legislation -- South Africa; Pension trusts -- Law and legislation -- South Africa; Social security beneficiaries -- South Africa